Patient Satisfaction Based on the Quality of Health Services Through Midwife Performance at the Batalaiworu Public Health Center: Case Study in Maternal and Child Health Clinic for Pregnant Women - Rasniah Sarumi; Albert Albert; Elna Sari; Hartati Hartati; Narmi Narmi; Astie Trisnawati (Poltekkes Kemenkes Palu, 2026)
Background: The quality of maternal health services at primary healthcare facilities remains a critical determinant of pregnant women’s service experiences and continued utilization of antenatal care (ANC). Inadequate service quality, particularly in terms of infrastructure, service processes, and interpersonal communication, may limit patient satisfaction and weaken the effectiveness of maternal health programs. Midwives play a central role in shaping service quality at Maternal and Child Health (MCH) clinics. This study aimed to examine the association between healthcare service quality and pregnant women’s satisfaction through midwife performance at the Batalaiworu Community Health Center, Southeast Sulawesi, Indonesia.Methods: A quantitative cross-sectional design was applied involving 51 pregnant women in Sidodadi Village, selected using saturated sampling. Data were collected using a structured questionnaire measuring healthcare service quality (structure and process dimensions) and patient satisfaction. Primary and secondary data were analyzed using the chi-square test to assess the association between variables.Results: Most respondents perceived healthcare service quality as good (72.5%), and 68.6% reported being satisfied with the services received. Bivariate analysis showed a statistically significant association between healthcare service quality and pregnant women’s satisfaction (ρ < 0.001). Pregnant women who perceived better service quality tended to report higher satisfaction levels, although some dissatisfaction persisted despite favorable service conditions.Conclusion: The findings indicate a significant association between healthcare service quality and pregnant women’s satisfaction at the primary healthcare level. These results highlight the importance of strengthening midwife performance, particularly in communication, responsiveness, and patient-centered care practices, alongside maintaining adequate service infrastructure. Continuous supervision and capacity-building initiatives for midwives are recommended to enhance maternal health service quality and patient satisfaction.